Edukasi Kesehatan Tentang Pencegahan Covid-19 dalam Mendukung Program Desa Tanggap Covid-19 - Fitria Saftarina; Dian Isti Angraini; Maya Ganda Ratna; Suharmanto Suharmanto; Rodiani Rodiani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Since the discovery of Covid-19, it has spread widely, causing a global pandemic that continues to this day. For this reason, promotive and preventive efforts are needed for the Karanganyar Village community regarding the prevention of Covid-19. This service aims to increase public knowledge about Covid-19 prevention. The target of the activity is 30 people. This community service activity was carried out using a health education, used presentation slides, leaflets, and videos. The results obtained showed that knowledge before education was 46.3 ± 8.9, and when health education was carried out, there was an increase in knowledge to 86.7 ± 9.2. From the results of the paired-t test analysis, it was found that p < 0.001, so that health education provided to the public about the prevention of Covid-19 could increase public knowledge. For practicing WHO handwashing practices correctly, 93.3% of participants were good at washing their hands. This activity needs to be carried out on an ongoing basis by the Puskesmas and Karanganyar Village governments in an effort to break the chain of transmission of Covid-19 and support the Covid-19 Response Rural Program.